Phylogenetic demonstration of two cases of perinatal human immunodeficiency virus type 2 infection diagnosed in adulthood - Barroso, H (2015)
HIV-2 infection was diagnosed in two patients 15 and 24 years of age and, thereafter, in their mothers. Epidemiological data suggested that vertical transmission was the most probable mode of infection in both patients (Mota-Miranda A, et al.: AIDS 2001;